Counseling Model Development Based on Analysis of Unwanted Pregnancy Case in Teenagers - Nugroho, Efa; Shaluhiyah, Zahroh; Purnami, Cahya Tri; Kristawansari, Kristawansari (KEMAS: Jurnal Kesehatan Masyarakat, 2017)
Teenegers who experience unwanted pregnancies are increasing. The number of client that access the Unwanted Pregnancy counseling services in IPPA Central Java in the year 2006 (94 clients), 2007 (91 clients), 2008 (95 clients), 2009 (68 clients), 2010 (157 clients), 2011 (98 clients), and 2012 (83 clients). Related to that data, 31% of clients were referred Haid Induction (HI), 3% refer shelter, and 66% continue the pregnancy and there were not identified. This research cunducted in 2014 used quantitative-qualitative approach which aimed to develop a model of counseling after mapping the case. Respondents were 5 Unwaned Prenancy counseling clients selected based on the final decision of counseling. From the research developed counseling model for teenage which should have an easy procedure, complete services, opening hours accordingly, no discrimination, respect privacy, provide pro choice, and low prices. Services consists of counseling, contraception, safe abortion, treatment of STIs, information center counseling and HIV testing, gynecological, prenatal and postnatal services, as well as the services of victims of gender based violence and sexual abuse.